Impact of environmental diversity of hunting complexes in the Lublin region on ontogenetic quality indicators in roe deer (Capreolus capreolus) - Czyżowski, Piotr (Biologia (Bratisl), 2018)
Populations of game are not confined to single ecosystems but function within higher-order units, e.g. ecological landscape. The basis for the establishment of the hunting complexes was the assumption that the existing game hunting grounds, i.e. the basic units implementing game management, are too small and do not cover the natural areas inhabited by game populations. Roe deer are flexible species and easily adapt to various site conditions, so they inhabit many different habitats, from large forest complexes, through small in-field tree stands and shrubs, to treeless grounds and field monocultures. The aim of the study was to determine a possible impact of environmental conditions prevailing in the hunting complexes of the Regional Directorate of State Forests (RDLP in Lublin) on the ontogenetic quality of roe deer. The study was conducted on 518 European roe deer (Capreolus capreolus) aged from 4 to 7 years (379 bucks and 139 does) harvested within hunting seasons 2010/2011–2013/2014. The results have shown that animals originating from areas with greater forest cover and denser stands are characterised by lower values of the mean ontogenetic quality parameters (carcase weight, kidney fat index, chest girth, weight of antlers) in comparison with animals from typical agricultural areas with fragmented forest complexes. These results indicate that, even in the case of such a eurytopic species as the roe deer, the ontogenetic quality differs between individual hunting complexes. The study has proved that strategies for hunting management of the roe deer should take into account the impact of the landscape structure, which provides a rationale behind creation of hunting complexes.